Amoebozoan testate amoebae illuminate the diversity of heterotrophs and the complexity of ecosystems throughout geological time - Porfirio-Sousa, Alfredo L.; Tice, Alexander K.; Morais, Luana [UNESP]; Ribeiro, Giulia M.; Blandenier, Quentin; Dumack, Kenneth; Eglit, Yana; Fry, Nicholas W.; Souza, Maria Beatriz Gomes E.; Henderson, Tristan C.; Kleitz-Singleton, Felicity; Singer, David; et al. (Proceedings of the National Academy of Sciences, 2024)
Heterotrophic protists are vital in Earth’s ecosystems, influencing carbon and nutrient cycles and occupying key positions in food webs as microbial predators. Fossils and molecular data suggest the emergence of predatory microeukaryotes and the transition to a eukaryote-rich marine environment by 800 million years ago (Ma). Neoproterozoic vase-shaped microfossils (VSMs) linked to Arcellinida testate amoebae represent the oldest evidence of heterotrophic microeukaryotes. This study explores the phylogenetic relationship and divergence times of modern Arcellinida and related taxa using a relaxed molecular clock approach. We estimate the origin of nodes leading to extant members of the Arcellinida Order to have happened during the latest Mesoproterozoic and Neoproterozoic (1054 to 661 Ma), while the divergence of extant infraorders postdates the Silurian. Our results demonstrate that at least one major heterotrophic eukaryote lineage originated during the Neoproterozoic. A putative radiation of eukaryotic groups (e.g., Arcellinida) during the early-Neoproterozoic sustained by favorable ecological and environmental conditions may have contributed to eukaryotic life endurance during the Cryogenian severe ice ages. Moreover, we infer that Arcellinida most likely already inhabited terrestrial habitats during the Neoproterozoic, coexisting with terrestrial Fungi and green algae, before land plant radiation. The most recent extant Arcellinida groups diverged during the Silurian Period, alongside other taxa within Fungi and flowering plants. These findings shed light on heterotrophic microeukaryotes’ evolutionary history and ecological significance in Earth’s ecosystems, using testate amoebae as a proxy.
Keywords: ancestral state reconstruction; Arcellinida; eukaryotic evolution; phylogenomics; vase-shaped microfossils